Design dispersed : forms of migration and flight - Dogramaci, Burcu; Pinther, Kerstin (Design (Transcript (Firm)), 2019)
This volume traces the complex and heterogeneous connections between migration and design in the 20th and 21st centuries. Questions tackled address the aesthetic effects that result from the networking, overlapping, and mixing of forms as well as the political and social dimensions of design: How are experiences of displacement inscribed in the things designers create? Can design contribute to a critical debate in migration and flight? Is it able to provide 'material' to rethink complex historical and cultural relationships?The chapters clarify the challenges and possibilities of thinking together migration, design and flight, critically historicize and discuss design concepts for displaced people, and bring mobile actors in design into focus.